Usability evaluation of an emergency department information system prototype designed using cognitive systems engineering techniques. (April 2017) - Clark, Lindsey N.; Benda, Natalie C.; Hegde, Sudeep; McGeorge, Nicolette M.; Guarrera-Schick, Theresa K.; Hettinger, A. Zachary; LaVergne, David T.; Perry, Shawna J.; Wears, Robert L.; Fairbanks, Rollin J.; Bisantz, Ann M.
Abstract: This article presents an evaluation of novel display concepts for an emergency department information system (EDIS) designed using cognitive systems engineering methods. EDISs assist emergency medicine staff with tracking patient care and ED resource allocation. Participants performed patient planning and orientation tasks using the EDIS displays and rated the display's ability to support various cognitive performance objectives along with the usability, usefulness, and predicted frequency of use for 18 system components. Mean ratings were positive for cognitive performance support objectives, usability, usefulness, and frequency of use, demonstrating the successful application of design methods to create useful and usable EDIS concepts that provide cognitive support for emergency medicine staff. Nurse and provider roles had significantly different perceptions of the usability and usefulness of certain EDIS components, suggesting that they have different information needs while working. Highlights: Novel design criteria for emergency department information systems is presented. Usability evaluation to determine usability, usefulness, and support for cognitive performance. Successful application of human factors engineering design methods. Displays regarding resource allocation received the highest ratings overall. Nurses and providers had significantly different ratings of displays for resource allocation.